ANTI-THYROGLOBULIN ANTIBODIES IN PATIENTS WITH AUTOIMMUNE THYROIDITIS DURING L-THYROXINE TREATMENT - O. A. Shashkova; I. Ya. Rudenko; A. A. Pinevich; A. R. Volkova; S. V. Dora; V. B. Klimovish (Медицинская иммунология, 2014)
Abstract. The presence of anti-thyroglobulin antibodies (AbTg) and their epitope specificity were investigated in sera of healthy people and patients with autoimmune thyroiditis (before and after L-thyroxine treatment). In sera samples AbTg were detected. It was shown that: (i) the level of AbTg in patients with autoimmune thyroiditis was significantly higher as compared with healthy individuals. After 6 months the level of AbTg of treated patients decreased but was higher than in healthy people. In serum samples of patients without L-thyroxine treatment the level of AbTg did not change. (ii) In healthy individual serum samples AbTg to antigenic regions of Tg recognized by monoclonal antibodies used in the work were not found. In patients serum samples monoclonal antibodies directed to 1F10 epitope were detected. Moreover the presence of monoclonal antibodies of the current specificity correlated with the increased level of AbTg. In 6 months the number of patients with AbTg to 1F10 epitope increased both in L-thyroxine treated and control group of patients. It is possible that the presence of AbTg to 1F10 epitope is associated with the pathological process in thyroid gland.